New advertising campaigns for women: Break or more of the same? - Brunelli, Anna Flora [UNESP]; Fossey, Marcela Franco (My University, 2018)
This paper analyzes a recent advertising piece targeted on women seeking to verify how the dialogue with the discourse against the beauty imperative is established. To this end, an interdisciplinary point of view is adopted, in which we assume the theoretical framework of French Discourse Analysis, and certain Social Psychology postulates about stereotypes, especially those of gender. With the analysis, the main goal was to verify, considering the image of women that emerges in the campaign, how a certain memory is mobilized for the interpretation of the advertising slogan and to what extent it is possible to assert that this piece stablish a rupture with the discourse that put a high value on the beauty imperative.
Novas campanhas publicitárias para mulheres: Ruptura ou mais do mesmo?
Keywords: Advertising discourse; Beauty imperative; Memory; Stereotypes